2018
DOI: 10.1155/2018/8412429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freeze-Thaw on a Midtemperate Soil Bacterial Community and the Correlation Network of Its Members

Abstract: Freeze-thaw (FT) events can influence soil functions. However, the overall impact of FTs on soil bacterial communities, especially in temperate regions, remains unclear. In this study, soil samples were collected from a midtemperate region in the northeast of China, and three incubation tests were then designed with varied FT amplitudes (i.e., at a freezing temperature of −15, −9, and −3°C, respectively), frequencies of FT cycles (i.e., under one, six, and 15 FT cycles, respectively) and soil water content (SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
4
12
2
Order By: Relevance
“…Accordingly, a meta-analysis suggested that FT events could significantly enhance soildissolved N pools and N mineralization but decrease microbial N [4]. In addition, the composition of bacterial communities could actively adjust after FT treatments, especially in temperate regions [5][6][7]. For example, the predominant phylum shifted from Actinobacteria to Proteobacteria and Gemmatimonadetes after FT treatments in our previous study [5].…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Accordingly, a meta-analysis suggested that FT events could significantly enhance soildissolved N pools and N mineralization but decrease microbial N [4]. In addition, the composition of bacterial communities could actively adjust after FT treatments, especially in temperate regions [5][6][7]. For example, the predominant phylum shifted from Actinobacteria to Proteobacteria and Gemmatimonadetes after FT treatments in our previous study [5].…”
Section: Introductionmentioning
confidence: 61%
“…In addition, our previous study found completely opposite changes in the bacterial communities in response to FT at two extremes of SWC [5]. Typically, the relative abundance of the active phylum Actinobacteria increased, decreased, and remained unchanged after FT in dry, normal, and wet soils, respectively [5]. Alternatively, as a diverse stress-tolerant bacterium, Acidobacteria changed in proportion contrariwise [5,14].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations